The impact of relationship marketing strategy on customer retention in a business-to-business services company - Lembede, Mashudu (My University, 2020)
Relationships are by nature two-sided, and both parties share the responsibility of the outcome. The antecedent state and the outcome may differ according to the perspective. This research focuses on understanding relationship marketing from the perspective of service industry businesses’ employees who interface with the customer. Relationship marketing theory suggests that successful relationship marketing strategy is a result of co-operative relationships with the customer, and its effectiveness is positively related to social and functional benefits. Trust and commitment are foundational in this theory; for this reason the variables investigated in this study are: trust, commitment, communication, and bonding, and their impact on relationship satisfaction. The influence of employee moderating factors, competency and responsiveness, on relationship satisfaction was also investigated. This construct was then proposed to affect customer retention. The research method utilised was a survey with a structured questionnaire, using convenience sampling of employees in an organisation. A total of 183 responses were received, comprising employees working across all levels in the company who interface with the customer. Structural equation modelling was then used to analyse the data. The results showed that trust and bonding were significantly influencing factors on relationship satisfaction, while commitment and communication were not significant. The employee moderating factors of competency and responsiveness were also found to be not significant in influencing relationship satisfaction. In turn, relationship satisfaction was found to be significantly positively influencing customer retention. Recommendations are given to organisations to strengthen their relationship marketing, particularly the employees interfacing with the customers, and directions for future research.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management,Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Relationship marketing; Relationship marketing strategy; Marketing; SDG-8: Decent work and economic growth